2019
DOI: 10.1080/15622975.2018.1555376
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune encephalitis with psychosis: Warning signs, step-by-step diagnostics and treatment

Abstract: Objectives: Despite intensive research, schizophrenia and schizoaffective disorders continue to be theoretical constructs that describe clinical syndromes and no pathophysiologically defined diseases. Moreover, there are no clear biomarkers at hand. Therefore, these diagnoses are still set up based on clinical ICD-10/DSM-5 criteria and the exclusion of alcohol-/drug-associated, systemic or other brain organic causes. Methods: Recently, autoimmune encephalitis with psychotic symptoms caused by specific antineur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 56 publications
0
54
1
1
Order By: Relevance
“…Fig. 2 Red flags that should lead to antibody diagnostics (according to [2,5,22,36,53,55,61,67,74,76,77,85]). EEG electroencephalography, MRI magnetic resonance imaging All serum-Ab findings should be interpreted in the context of extended history data, the clinical syndrome, and the examination findings (especially including CSF Ab testing; [51,82,85] Compared to MRI, FDG-PET possibly has higher sensitivity for inflammatory changes ( [5,28,35]; Fig.…”
Section: Indication For Antibody Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 2 Red flags that should lead to antibody diagnostics (according to [2,5,22,36,53,55,61,67,74,76,77,85]). EEG electroencephalography, MRI magnetic resonance imaging All serum-Ab findings should be interpreted in the context of extended history data, the clinical syndrome, and the examination findings (especially including CSF Ab testing; [51,82,85] Compared to MRI, FDG-PET possibly has higher sensitivity for inflammatory changes ( [5,28,35]; Fig.…”
Section: Indication For Antibody Analysesmentioning
confidence: 99%
“…The risk for extrapyramidal motor side effects seems to be increased in patients with AEs [49,67,76,77]. Therefore, psychotic symptoms in the context of AP can be symptomatically treated with antipsychotics with a low risk for motor side effects [76,77]. Benzodiazepines can be used for anxiolysis and sedation and, in higher doses, for the treatment of catatonic symptoms [76,77].…”
Section: Symptomatic Treatmentmentioning
confidence: 99%
“…Considering the potential relationship between antibody status and immune injury, we speculate that the body suffer immune injury might easier to induce the occurrence of other immune diseases, those conditions are existed in antibody-positive AE which was reported by Ohkawa T [22][23], but not in antibody-negative AE, although further investigations are needed. Furthermore, the state of antibodies may reflect the severity of immune damage, as found by others that the antibody level could be reduced as the improvement of symptoms [10].…”
Section: Discussionmentioning
confidence: 75%
“…Immunotherapy plays a key role in the treatment of autoimmune epilepsy. 3,5,16,[22][23][24] A study of 29 patients with anti-LGI1 encephalitis by Sarosh et al found that immunotherapies showed a remarkable reduction in FBDS frequency 21 . Among 27 patients receiving immunotherapy, 14 patients (52%) showed a > 50% reduction in seizure frequency.…”
Section: Discussionmentioning
confidence: 99%